Analisis Yuridis Penegakan Hukum Migran Ilegal di Luar Negeri Korban Perdagangan Manusia : Studi Penelitian di Polsek Nongsa Kota Batam - ., Primajaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The crime of human trafficking is a transnational crime. Human trafficking is generally carried out by violating human rights, such as in the form of cruel treatment and slavery-like practices. The issues in this research are how the law regulates the enforcement of illegal migrant workers abroad who are victims of human trafficking, how the implementation of law enforcement for illegal migrant workers abroad who are victims of human trafficking is carried out, and what are the obstacles and solutions for law enforcement for illegal migrant workers abroad who are victims of human trafficking by conducting a research study at the Nongsa Police Station in Batam City. Meanwhile, this research aims to determine the regulation of law enforcement for illegal migrant workers abroad who are victims of human trafficking, to understand how the implementation of law enforcement for illegal migrant workers abroad who are victims of human trafficking is carried out, and to identify the obstacles and solutions for law enforcement for illegal migrant workers abroad who are victims of human trafficking in the research study at the Nongsa Police Station in Batam City. This research uses a descriptive method with a normative approach (legal research) to obtain primary data through field research. The results of the study show that the enforcement of law for illegal migrant workers abroad who are victims of human trafficking in the research study at the Nongsa Police Station in Batam City has been carried out well, although there are still many challenges in the field, especially the lack of legal awareness among prospective migrant workers/Indonesian migrant workers, weak law enforcement, and inadequate supervision system for Indonesian migrant workers abroad. It is hoped that the Government (BP2TKI) or PPTKIS should not only provide education and training for competency and language, but also provide guidance and advocacy to increase legal awareness and legal protection for prospective migrant workers/Indonesian migrant workers.